An Eploratory Analysis of the Management Capacity Within the Local Public Administration from Romania - Horia Mihai RABOCA; Ioan LAZĂR; Paul Sorin LAZĂR; Diana ZAGAN-ZELTER (Transylvanian Review of Administrative Sciences, 2010)
The present paper aims at analyzing the development level of the management capacity within the local public institutions from Romania. The purpose and the objectives of the paper are to emphasize the general picture of the management capacity of the local public institutions, respectively to highlight not only the main characteristics of the management capacity but also the major factors that influence the development level of this capacity. The results of the research presented in the paper show that at least the management capacity from the local public institutions is influenced by a number of factors.